Immune Checkpoint Inhibitors Combined With Chemotherapy Compared With Chemotherapy Alone for Triple-Negative Breast Cancer: A Systematic Review and Meta-Analysis - Ji, Qiao; Ding, Jingxian; Hao, Meiqi; Luo, Nachuan; Huang, Jiabing; Zhang, Wenxiong (Frontiers in Oncology, 2021)
Background: It is still controversial whether immune checkpoint inhibitors (ICIs) can improve the curative effect when added to original standard chemotherapy treatment for triple-negative breast cancer (TNBC). We compared their antitumor efficacy and adverse effects (AEs) to make a better clinical decision. Methods: Seven databases were searched for eligible articles. Progression-free survival (PFS), overall survival (OS) and AEs were measured as the primary outcomes. Results: Nine randomized controlled trials (RCTs) involving 4501 patients were included. ICI+chemotherapy treatment achieved better PFS (hazard ratio [HR]: 0.78, [0.70-0.86], p < 0.00001), OS (HR: 0.86, [0.74-0.99], p = 0.04), and complete response (584/1106 vs. 341/825, risk ratio [RR]: 1.38, [1.01-1.89], p = 0.04). With the prolongation of survival, the survival advantage of ICI+chemotherapy increased compared with chemotherapy. Subgroup analysis suggested that the addition of ICIs might not have a better effect in Asian patients, patients with locally advanced disease or patients with brain metastases. In the toxicity analysis, more Grade 3-5 AEs and serious AEs were found in the ICI+chemotherapy group. For Grade 3-5 AEs, more cases of diarrhea, severe skin reactions, pneumonitis, hepatitis and adrenal insufficiency were related to the ICI+chemotherapy group. Conclusions: ICI+chemotherapy appears to be better than chemotherapy alone for TNBC treatment, with better OS and PFS. However, its high rates of serious AEs need to be taken seriously.